Impact of Fc N-linked glycans on in vivo clearance of an immunoglobulin G1 antibody produced by NS0 cell line. Issue 1 (1st January 2020) - Kim, Jun; Luo, Haibin; White, Wendy; Rees, William; Venkat, Raghavan; Albarghouthi, Methal
ABSTRACT: The heterogeneity of glycosylation on therapeutic monoclonal antibodies (mAbs) may affect the safety and efficacy of these agents. In particular, glycans of nonhuman origin, such as galactose-alpha-1, 3-galactose (gal-α-gal) and N -glycolylneuraminic acid (NGNA), in the Fc region of therapeutic mAbs produced from murine cell lines carry a risk of immunogenicity. Immunogenic glycan structures can have immune-mediated clearance, resulting in faster clearance from in vivo circulation than non-immunogenic structures. To demonstrate the impact of these Fc nonhuman glycans on in vivo clearance, we purified and analyzed the glycan profile of a monoclonal antibody (mAb1) from human serum samples collected from clinical study participants. We purified mAb1 in a three-step chromatographic separation process (protein A, immobilized anti-mAb1 antibody affinity, and weak cation exchange chromatography) and extracted and labeled its N-linked oligosaccharide structures with 2-aminobenzamide acid for analysis on ultrahigh-performance hydrophilic interaction liquid chromatography. A comparison of the glycan profile of mAb1 recovered from human serum on the same day and 4 weeks after dosing revealed no significant differences, indicating similar clearance of mAb1 with nonhuman gal-α-gal or NGNA glycan in the Fc region compared with the human glycans. The relative proportions of the glycans remained similar, and all patients who had already received multiple doses of mAb1 over the course of a year were negative for antidrug antibodies, suggesting that none of the glycans induced an immune response. Therefore, we concluded that mAb1 gal-α-gal and NGNA glycoforms represent a low risk of conferring immunogenicity.